Book Review of Mathers and St-Cyr's Pinasuutitsaq ᐱᓇᓲᑎᑦᓴᖅ: Reference Guide for Career Development Counsellors Working With Inuit Clients - Tipple, Stephanie D. (Canadian Journal of Counselling and Psychotherapy, 2022)
Combining the voices of practitioners within the field and information from the literature, Pinasuutitsaq ᐱᓇᓲᑎᑦᓴᖅ: Reference Guide for Career Development Counsellors Working With Inuit Clients is a concise, reader-friendly resource that will assist career development counsellors in their work with Inuit clients. Given the complex employability challenges experienced by many Inuit communities, culturally appropriate interventions and approaches are essential, as highlighted by the Truth and Reconciliation Commission of Canada. Funded by the Regroupement québécois des organismes pour le développement de l’employabilité, this reference guide focuses on the approaches and interventions utilized at the Ivirtivik Centre, which offers services to Inuit clients in Montreal and in Nunavik, Quebec. The guide is divided into four chapters, each offering topic-specific information, important highlights, external resources, Nunavik-specific resources, and sample interventions and activities to assist career development counsellors in working with Inuit clients effectively from a social justice framework.